Perubahan Sosial Keagamaan di Kecamatan Pelayangan Kota Jambi - Qodri, Maryani Muhammad (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
This article examined the impact of the development of sub-district Pelayangan that had spawned the social dynamics of local community life. One form of social changed the reduction of symptoms of religious education, adherence to scholars also gradually faded. In addition, changed also occur in the religious traditions, modernization teen fashion clothing, as well as patterns of thought and patterns of social relationships tend to be pragmatic. The social changed occur due to factors of development of transport infrastructure, especially bridges Batanghari II, construction of public schools, increasing the level of public education, governmentrun development policy, as well as contact with the culture of the outside district of Pelayangan. Such changed generally had implications on the shifting social norms and structures district of Pelayangan. However, the relative Pelayangan society could cope with change in the religious aspects of culture through the screening process, so that new elements could be integrated with the old elements, keeping the old elements of good and absorbing new elements that suit their needs.